2015
DOI: 10.1007/s11869-015-0356-1
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the exposure metric in air pollution epidemiology studies: When does it matter, and why?

Abstract: Exposure error in ambient air pollution epidemiologic studies may introduce bias and/or attenuation of the health risk estimate, reduce statistical significance, and lower statistical power. Alternative exposure metrics are increasingly being used in place of central-site measurements, with the intent of reducing exposure error. Dependent on the study design, health outcome, and pollutant of interest, these metrics may provide a means of reducing error (leading to less bias and uncertainty in health risk estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that the spatial distribution of traffic-related air pollution is generally stable over periods 10-15 years, supporting the use of an annual average of a single year preceding our questionnaire to assess long-term exposure (Eeftens et al 2011;Gulliver et al 2011). Also the air pollution model was raster-based (100mx100m) and this may have led to exposure misclassification and lower correlations (Dionisio et al 2016). The question on subjective perception of air pollution in the questionnaire referred to air pollution in the neighbourhood of home or work, yet we only tested out the relationship at the home address, which again may have blurred the results.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown that the spatial distribution of traffic-related air pollution is generally stable over periods 10-15 years, supporting the use of an annual average of a single year preceding our questionnaire to assess long-term exposure (Eeftens et al 2011;Gulliver et al 2011). Also the air pollution model was raster-based (100mx100m) and this may have led to exposure misclassification and lower correlations (Dionisio et al 2016). The question on subjective perception of air pollution in the questionnaire referred to air pollution in the neighbourhood of home or work, yet we only tested out the relationship at the home address, which again may have blurred the results.…”
Section: Discussionsupporting
confidence: 63%
“…The principle idea of exposure is the combination of pollutant concentration values in the environments where people spend their time, and the amount of time they spend within them [4]. Thus, the introduced approaches to model urban-scale ambient pollutant concentrations and generic TMA models need to be combined to calculate meaningful exposure metrics [84], such as total population exposure or population-weighted population exposure (PWE).…”
Section: Population Exposure Modelingmentioning
confidence: 99%
“…Previous health studies that use atmospheric models have been conducted at coarser geographic scales (e.g., GEOS-Chem) and have considered only fire-derived pollutants rather than fire in conjunction with PM from other sources (e.g., traffic, utilities) when assessing associations with health, which may overestimate the fire-specific exposures [60,73]. Other studies have used atmospheric modeling in conjunction with adjustments from air quality monitoring data, satellite remote sensing data or additional post-processing statistical techniques [68,71,[74][75][76][77][78][79].…”
Section: Spatiotemporal Smoke Exposure Approachesmentioning
confidence: 99%